2022
DOI: 10.1161/hypertensionaha.122.19377
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Confirmatory Tests for Diagnosing Primary Aldosteronism: a Systematic Review and Meta-Analysis

Abstract: Background: Confirmatory tests are recommended for diagnosing primary aldosteronism, but the supporting evidence is unclear. Methods: We searched Medline, EMBASE, and the Cochrane Central Register of Controlled Trials. Studies evaluating any guideline-recommended confirmatory test (ie, saline infusion test, salt loading test, fludrocortisone suppression test, and captopril challenge test), compared with a reference standard were included. The Quality As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 88 publications
(195 reference statements)
1
16
0
1
Order By: Relevance
“…The significance of confirmatory testing has recently been questioned from the perspective of PA management. In a very recent report, the evidence for confirmatory testing in PA diagnosis was based on very low‐quality evidence 26 . In addition, it has been reported that PA is a spectrum and that the distinction between biochemically overt PA and renin‐independent aldosterone production is an arbitrary construct limited to identifying the most severe type of PA 27,28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of confirmatory testing has recently been questioned from the perspective of PA management. In a very recent report, the evidence for confirmatory testing in PA diagnosis was based on very low‐quality evidence 26 . In addition, it has been reported that PA is a spectrum and that the distinction between biochemically overt PA and renin‐independent aldosterone production is an arbitrary construct limited to identifying the most severe type of PA 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…In a very recent report, the evidence for confirmatory testing in PA diagnosis was based on very low-quality evidence. 26 In addition, it has been reported that PA is a spectrum and that the distinction between biochemically overt PA and renin-independent aldosterone production is an arbitrary construct limited to identifying the most severe type of PA. 27,28 It is difficult to completely exclude PA with one type of confirmatory test owing to its sensitivity, and this study may have ruled out some low-renin hypertensive patients with milder aldosterone secretion. We recently found that patients with discordant results between SIT and CCT as confirmatory tests have a high probability (95.5%) of bilateral subtype of PA on AVS.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific evidence supporting the usefulness of these tests is very weak. In fact, two large independent meta-analyses of the studies with the more solid design concluded that they are unreliable, not adequately validated and, therefore, should not be performed [52,53]. Moreover, these tests, which are based on the premise that aldosterone-secreting tissues in PA are autonomous from angiotensin II [54], a totally unproven hypothesis, cause special problems in patients with RH, who, by definition, are on multiple drugs interfering with angiotensin II formation or action.…”
Section: Issues In the Diagnostic Work-up Of Primary Aldosteronism In...mentioning
confidence: 99%
“…Screening tests for PA should be done in patients with very high values of arterial hypertension (ideally before starting anti-hypertensive drugs), resistant HBP, HBP and hypokalaemia, adrenal incidentaloma, as well as individuals who had a family history of HBP or strokes at young ages (before 40 years old) or PA [ 83 , 84 , 85 , 86 , 87 , 88 ]. After identification of a high aldosterone/renin ratio, confirmatory tests (saline infusion test or captopril test) may follow the screening assays, but not necessarily, unless spontaneous or diuretic-induced severe hypokalaemia or highly suggestive plasma aldosterone levels with suppressed renin values are presented and highly suggestive for the diagnostic [ 83 , 84 , 85 , 86 ]. Additionally, an ACTH stimulation test might distinguish between aldosteronoma and a bilateral PA disease, but not all studies agree [ 89 ].…”
Section: Approach Of Connshing Syndromementioning
confidence: 99%
“…Rarely, the evaluation of cortisol circadian rhythm and DXM suppression test with higher doses (like 2 mg) are necessary [ 90 ]. As mentioned, steroids metabolomics represent the next step in approaching adrenal tumours, especially entities like Connshing syndrome [ 83 , 91 ].…”
Section: Approach Of Connshing Syndromementioning
confidence: 99%